(untitled) (Analysis in Theory and Applications, 2021)
The existence of an infinite sequence of sign-changing solutions are proved for a class of quasilinear elliptic equations under suitable conditions on the quasilinear coefficients and the nonlinearity where ΩR^N is a bounded domain with smooth boundary, and we use The main interest of this paper is for the case of bounded quasilinearity b_ij. The result is proved by an elliptic regularization method involving truncations of both u and the gradient of u.